EduChem Hidrokarbon: A Green Chemistry Based Discovery Learning Media on Hydrocarbon Nomenclature - Hardiyanti, Siti; Rijai, Laode; Herliani, Herliani (FKIP Universitas Lampung, 2022)
This study aims to develop Educhem Hydrocarbons based on Green Chemistry using the Discovery learning learning model on the nomenclature of hydrocarbon compounds. This study applies the Research and Development (R&D) method with the Brog and Gall approach. The research sample amounted to 44 students of class XI. The instruments used are validation questionnaires, student response questionnaires, pretest posttest questions and student activity observations. The results show that the learning media is declared valid with a validity value of 93.93%, practical with a small scale of 89.76% and 93.53% of a large scale. The effectiveness of the media based on the value of small-scale N-gain 0.71 and large-scale N-gain 0.73. The effectiveness based on student activities on a small scale is 90.71% and a large scale is 92.99%. This shows that the Educhem Hydrocarbons learning media based on Green Chemistry is declared suitable to be used as a learning resource on the subject of nomenclature of hydrocarbon compounds. Keywords: learning media, discovery learning, green chemistry, hydrocarbon nomenclature.DOI: http://dx.doi.org/10.23960/jpmipa/v22i2.pp276-283